2020
DOI: 10.1055/s-0040-1709522
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Enriched Population Pharmacokinetic Model for Recombinant Factor VIII-Fc Fusion Protein Concentrate in Hemophilia A Patients

Abstract: Background The currently published population pharmacokinetic (PK) models used for PK-guided dosing in hemophilia patients are based on clinical trial data and usually not externally validated in clinical practice. The aim of this study was to validate a published model for recombinant factor VIII-Fc fusion protein (rFVIII-Fc) concentrate and to develop an enriched model using independently collected clinical data if required. Methods Clinical data from hemophilia A patients treated with rFVIII-Fc co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…Population PK models of the concentrates published in the literature were used by the Monte Carlo method to simulate the FVIII level versus time profiles. 12,[17][18][19][20][21] The PK parameters and equations used in the population PK models are presented in ►Supplementary Tables S1 to S4 (available in the online version).…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Population PK models of the concentrates published in the literature were used by the Monte Carlo method to simulate the FVIII level versus time profiles. 12,[17][18][19][20][21] The PK parameters and equations used in the population PK models are presented in ►Supplementary Tables S1 to S4 (available in the online version).…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…[14][15][16] Fortunately, population PK models of the various FVIII concentrates have been published or are publicly available that describe the PK of the FVIII concentrates in a typical patient as well as the intraand interindividual variability. [17][18][19][20][21] With these population PK models, Monte Carlo simulations can be performed. In this manner, individual PK profiles of a virtual population are obtained that match the patient characteristics of the population from which the model was constructed, while no costs are made and patients are not exposed to therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in an increase of FVIII levels from 100 IU/dL when measured by OSA compared with 131 IU/dL when measured by CSA. 24 Because reagents have been identified as the most important cause of assay variability, 16 it is striking that we were not able to identify the used reagent of 11/27 models. Interestingly, we identified 16 different documented reagents.…”
Section: Laboratory Datamentioning
confidence: 97%
“…19 In Bukkems et al, it was shown that population clearance and central volume of distribution were underpredicted in patients aged ,12 years when applying a population PK model based solely on patients 12 years and older. 24 Overweight and obese adults are represented in most models. This is clinically relevant because of the increasing prevalence of overweight/ obesity in 31% of hemophilia patients in Europe and North American, with concomitant risks of under-or overdosing of factor concentrates.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation